Design and Realization of Smart Plug Based On QR Code and WIFI Access - Gistya Sudiartama, Annenta; Darlis, Denny; Hartaman, Aris (Greenation International Journal of Engineering Science, 2023)
The traditional electrical outlet has evolved with the emergence of "smart plugs," which are WiFi-based devices controlled through communication networks. Many innovations and studies have explored the use of smart plugs for remote load control via the internet and some even utilize renewable energy sources like solar power. In this research, we present a smart plug equipped with a QR code control feature, allowing users to manage connected loads efficiently. Additionally, the smart plug includes sensors to measure power consumption, displaying real- time data on the connected devices. Our smart plug system incorporates an ESP32 microcontroller as the core unit and ACS712 and ZMPT101B sensors for electric current and voltage measurements, respectively. The parameters calculated are electric current and voltage, enabling users to monitor energy consumption accurately. Through rigorous testing, we evaluate the accuracy of the ACS712 and ZMPT101B sensors. The results indicate a 11,39% error for electric current measurements using the ACS712 sensor and a 0,022% error for voltage measurements with the ZMPT101B sensor. This research introduces an innovative smart plug that allows control via a QR code and provides real-time power and load information.